Pengaruh Budaya Organisasi, Fleksibilitas Kerja, dan Pelatihan Kerja terhadap Kepuasan Kerja Karyawan di Rumah Sakit Efarina Etaham Berastagi - Surbakti, Denada Sari; Silalahi, Sahat Parulian Remus; Sihite, Mislan (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2025)
This study aims to test and analyse the influence of organisational culture, work flexibility, and job training on employee job satisfaction at Efarina Etaham Berastagi Hospital. The research method used in this research is quantitative descriptive research method. The sample in this study were 150 respondents. Based on the results of the t hypothesis test, it can be concluded that organisational culture partially has a positive and significant effect on job satisfaction, work flexibility partially has a positive and significant effect on job satisfaction, job training partially has a positive and significant effect on job satisfaction. Based on the results of the F hypothesis test, it can be concluded that organisational culture, work flexibility, and job training together or simultaneously have a significant effect on employee job satisfaction. Based on the results of the coefficient of determination analysis, it is known that the adjusted R-square value is 0.838. Based on this value, organisational culture, work flexibility, and job training are able to influence job satisfaction by 58.1%, the remaining 41.9% is explained by other variables or factors.